Tailoring sustainable materials: Investigating nanoclay effects on citric acid crosslinked waste coconut fiber reinforced modified vegetable oil composites - Jurita Baishya; Tarun K. Maji (Waste Management Bulletin)
Sustainability concerns are driving industries to focus on eco-friendly substitutes for polymers and plastics. Waste fibers and bio-based materials are increasingly becoming popular as renewable options. They help lower carbon footprints and reduce reliance on fossil fuels. These materials also tackle environmental problems and support resource conservation and waste reduction. The primary objective of this endeavor is to develop green composites from coconut fiber, an abundant and underutilized byproduct of the coconut industry. This study assesses the effect of incorporating nanoclay at varying weight percentages (1, 3, and 5 wt%) on the properties of Coconut Fiber (CF) reinforced composites. The composites are fabricated using a compression molding process, with Methacrylic Anhydride modified Epoxidized Linseed Soybean Oil (MAELSO) serving as the polymer matrix, and Citric Acid (CA), a naturally derived crosslinker obtained from citrus fruits, to enhance the bonding within the material. The interaction between MAELSO, CF, CA and nanoclay was determined by Fourier Transform Infrared (FTIR) spectroscopy. X-ray Diffraction (XRD) and Transmission Electron Microscopy techniques (TEM) were employed to investigate the delamination and dispersal of silicate layers. Evaluation of surface morphology was achieved by Scanning Electron Microscopy (SEM) technique. The nanoclay-filled composites exhibited better mechanical property, higher thermal stability and flame retardant property compared to the nanoclay-free composites. Among all the nanocomposites those loaded with 1 wt% of nanoclay, exhibited the least amount of water vapor absorption capacity, volumetric swelling, and highest chemical resistance. The significance of this study lies in that the resulting composites promote sustainability by utilizing waste, renewable resources and biodegradable materials. This approach minimizes environmental impact while maintaining performance. As an eco-friendly alternative, these composites provide a viable substitute for conventional, non-biodegradable synthetic materials, supporting both environmental conservation and advanced material performance. The developed green composites demonstrate potential for construction and household applications due to their improved mechanical strength, thermal stability, and flame retardancy. Their low water absorption and improved chemical resistance make them suitable for humid environments, supporting sustainable material innovation.